RISK OF SUSTAINABILITY APPLE FARMING IN PONCOKUSUMO VILLAGE, PONCOKUSUMO SUB-DISTRICT, MALANG REGENCY - Muhammad Syafri Syafreza Hasyim; Neza Fadia Rayeza; Dina Novia Priminingtyas (Socio-Economics/Agribusiness Department, 2023)
Sustainability is one thing that becomes the benchmark for a farming business. The concept of sustainability is based on three mutually supportive and interrelated dimensions of sustainability, namely the economic, social, and ecological. Risk management is also necessary for maintaining the sustainability of a farming business. Risk management that is implemented properly can help avoid adverse events and increase the chances of success in a business. This research was conducted in Poncokusumo village, Poncokusumo district, Malang regency. This study aimed to analyze the risk of sustainability of apple farming in Poncokusumo Village according to internal (strengths and weaknesses) and external (opportunities and threats) factors and the level of risk faced. Also, to formulate alternative mitigation to deal with it. This study used a sample of 22 apple farmers in Poncokusumo village. The data analysis technique used is the SWOT analysis and the risk assessment matrix. Based on the analysis, 5 risks of apple farming have a very high level of risk according to the risk assessment matrix, namely the quality of production, product selling price, pests, plant diseases, and climate uncertainty. According to the SWOT analysis, the risk of sustainability of apple farming faced by apple farmers in Poncokusumo village in terms of strength has a value of 1.10 and weakness of 0.12 (internal factors). The opportunity section has a value of 0.87 and a threat of 0.10 (external factors). The right strategy to overcome the risks that occur is to implement sustainable agriculture.